STRATEGI PEMENANGAN PARTAI POLITIK DALAM PEMILU (Study kasus Partai Keadilan Sejahtera dan Partai Keadilan dan Persatuan Indonesia di Kota Salatiga dalam Pemilu 2009) - Insan Mahmud (Program Magister Ilmu Politik, Universitas Diponegoro, 2018)
General election 2009 representing third general election which carried out after reform ’ 98 with the better general election system compared to two previous general election systems, among other things is applying of order of certain parliamentary threshold and chosen legislative candidate determination with the majority of votes. Consequently, each political party had to make the strategy to win the general election which is as effective as possible to be coming up as winner in every level of election area. This research represent the research qualitative which aim to describe and compare the winning strategies of Partai Keadilan dan Persatuan Indonesia (PKPI) and Partai Keadilan Sejahtera (PKS) at Salatiga city in 2009’s general election. PKPI And PKS represent the political party that was following the general election 2004 having chair which significant in Salatiga city. The research findings stresses that both parties have unique strategies when deal with the game rules, particularly with DPP (Board of Province Directors) and DPK (Board of Town Directors). Furthermore, both were also attempting to recruit candidates and trying to campaign their programs competitively in the city.